2015
DOI: 10.1186/s12967-015-0681-z
|View full text |Cite
|
Sign up to set email alerts
|

SLC39A6: a potential target for diagnosis and therapy of esophageal carcinoma

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is a highly lethal cancer, and its underlying molecular mechanisms are poorly understood. Recent large-scale genome-wide association studies in Chinese Han populations have identified an ESCC susceptibility locus within the SLC39A6 gene. Here, we sought to explore the expression and biological function of SLC39A6 in ESCC.MethodsMultiethnic validation of SLC39A6 protein expression was performed in different cohorts of patients from Chinese Han and Kazakh popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…CTGF protein expression was notably correlated to poor survival of ESCC patients after 12 years of follow‐up . An atypical expression pattern of SLC39A6 and PFN2 was observed between different lesion stages, showing that high expression of SLC39A6 and PFN2 was associated with shorter overall survival . Low expression of certain proteins has also been associated with poor prognosis.…”
Section: Potential Protein Biomarkers For the Prognosis Of Esccmentioning
confidence: 94%
See 3 more Smart Citations
“…CTGF protein expression was notably correlated to poor survival of ESCC patients after 12 years of follow‐up . An atypical expression pattern of SLC39A6 and PFN2 was observed between different lesion stages, showing that high expression of SLC39A6 and PFN2 was associated with shorter overall survival . Low expression of certain proteins has also been associated with poor prognosis.…”
Section: Potential Protein Biomarkers For the Prognosis Of Esccmentioning
confidence: 94%
“…These studies suggest that deregulated proteins with no obvious linear patterns (i.e., not trending up or down) could be potential biomarkers, and that focusing on distinct precancerous lesions rather than invasive carcinoma may help uncover new potential protein biomarkers for early detection. Another study reported an atypical expression pattern of SLC39A6 and profilin 2 (PFN2) at different stages; SLC39A6 and PFN2 expression increased in succession from normal to LGIN, to ESCC, and, finally, reached their peak in HGIN lesions, suggesting the potential diagnostic role of SLC39A6 and PFN2 in ESCC …”
Section: Potential Protein Biomarkers For Escc and Precancerous Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…SLC39A6 protein a member of a new subfamily of zinc transporters, is involved in maintaining the intracellular homeostasis of zinc, an ion that is essential in the control of gene transcription, differentiation, development and growth, suggesting that its altered distribution might promote tumorigenesis and targeting SLC39A6 might be a potential therapeutic strategy [24]. The Transient Receptor Potential (TRP) channels family which consists of seven different subfamilies, namely TRPC (Canonical), TRPV (Vanilloid), TRPM (Melastatin), TRPML (Mucolipin), TRPP (Polycystin), and TRPA (Ankyrin transmembrane protein) and TRPN (NomPC-like), are related to several physiological and pathological processes.…”
Section: Targets Of Cancer Diagnosis: Molecular Basismentioning
confidence: 99%